2018
DOI: 10.1002/slct.201801050
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis, Antimicrobial Activity and Cytotoxicity of Novel Fused Pyrimidine Derivatives Possessing a Trifluoromethyl Moiety

Abstract: A series of novel fused pyrimidine derivatives possessing a trifluoromethyl moiety have been synthesized by the reaction of the enaminone named E‐3‐(dimethylamino)1‐(4‐(trifluoromethyl)phenyl)prop‐2‐en‐1‐one with a variety of heterocyclic amines under solvent free mechanochemical condition utilizing nano sized magnesium oxide catalyst. 1H–15N HMBC (Heteronuclear Multiple Bond Correlation) NMR technique was used to allow for the unambiguous structural characterization of the fused pyrimidine products. The newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…[62][63][64] Most of these studies have been focused on developing alternative synthetic routes to marketed APIs, for which the benefit-risk balance was already known, [9b, 65,66] and therefore the mechanochemical procedures were preordained to provide products previously regarded as safe. However, in some cases, newly mechanosynthesized molecules and pharmaceutical solid forms have been studied to determine their biological activity, [67][68][69][70][71][72] toxicity, [73,74] and stability. [75][76][77] For example, a recent work focused on developing a ball milling route to access Cu II metallodrugs [Cu(HMeI) 2 (solvent)x; HMel = meloxicam; solvent = DMF, DMSO, H 2 O] revealed that mechanochemistry had led to the formation of a novel Cu II complex of octahedral geometry instead of the typical square-pyramidal complex obtained in solution.…”
Section: Gc 4: Designing Safer Chemicalsmentioning
confidence: 99%
“…[62][63][64] Most of these studies have been focused on developing alternative synthetic routes to marketed APIs, for which the benefit-risk balance was already known, [9b, 65,66] and therefore the mechanochemical procedures were preordained to provide products previously regarded as safe. However, in some cases, newly mechanosynthesized molecules and pharmaceutical solid forms have been studied to determine their biological activity, [67][68][69][70][71][72] toxicity, [73,74] and stability. [75][76][77] For example, a recent work focused on developing a ball milling route to access Cu II metallodrugs [Cu(HMeI) 2 (solvent)x; HMel = meloxicam; solvent = DMF, DMSO, H 2 O] revealed that mechanochemistry had led to the formation of a novel Cu II complex of octahedral geometry instead of the typical square-pyramidal complex obtained in solution.…”
Section: Gc 4: Designing Safer Chemicalsmentioning
confidence: 99%
“…This method is devoid of the use of other harmful/toxic organic solvents and follows an environmentally benign protocol resulting in easy and feasible access to develop novel polysubstituted azoloazine derivatives. [33] Here, it is noteworthy to mention that the group was able to carry out the characterization of the synthesized molecules using HMBC 1H-15N NMR technique, confirming the formation of regioisomers, and it was characterized unambiguously. This characterization technique was much more feasible than the conventional single-crystal X-ray diffraction crystallography as these types of compounds had a large number of regioisomers.…”
Section: Synthesis Of Pyrazolopyrimidines Under Solvent-free Conditionsmentioning
confidence: 83%
“…To the best of our knowledge, few reports dealt with a heterogeneous catalyst system for this 1,4-conjugate addition [28][29][30]. Bearing in mind all of the abovementioned factors, we continued our interest in introducing a benign protocol for organic reactions utilizing heterogeneous catalysts [20,[31][32][33][34]. We introduce here a facile sonochemical synthesis for the conjugate addition of aryl halides onto electron-deficient olefins utilizing a CoMgAl LDH.…”
Section: Introductionmentioning
confidence: 99%